CONSTRIBUTION OF WOMEN'S ROLE IN SELF-ACUALIZING IN THE COMMUNITY ORGANIZATIONAL GROUP OF MEDAN CITY - Nur Aisyah; Wan Suryani (PROCEEDING UMSURABAYA, 2022)
North Sumatra has a population of 14.8 million, and the municipality of Medan has 2.4 million, consisting of 1.21 million men and 1.22 million women. There are more women than men, with the assumption that women are more likely to show self-actualization. The purpose of this research is how the contribution of women's role in self-actualization in the community organizations of the city of Medan. This study uses data collection methods through qualitative research case interviews through informants. The subjects of this study were 4 women who are members of the IWAPI organization, FKMI. The results showed that women's self-actualization is the potential that a person has, especially women, to realize and maximize their potential, in this case the women in the IWAPI organization, FKMI and have chosen and determined the appropriate choice of forum and are able to position themselves as women who actualize themselves. The embodiment of women's self-actualization in community organizations at the Indonesian Women Entrepreneurs Association (IWAPI) and the Indonesian Muslimah Communication Forum (FKMI) which contribute to the realization of self-actualization by exploring their potential in encouraging the economy during the covid19 pandemic. Based on observations and documentation of data from female researchers at the IWAPI organization, FKMI, it was found that along with the impact of the COVID-19 pandemic, encouraging self-improvement through self-actualization in encouraging an increase in family income and the life of the people of MedanKeywords                    : Contribution; self-actualization, women; Medan City